Deficit hysteria redux? Why we should stop worrying about US government deficits - Yeva Nersisyan; L. Randall Wray (Levy Economics Institute of Bard College, 2010)
This brief by Yeva Nersisyan and Senior Scholar L. Randall Wray argues that deficits do not burden future generations with debt, nor do they crowd out private spending. The authors base their conclusions on the premise that a sovereign nation with its own currency cannot become insolvent, and that government financing is unlike that of a household or firm. Moreover, they observe that automatic stabilizers, not government bailouts and the stimulus package, have prevented the US economic contraction from devolving into another Great Depression. The authors dispense with unsubstantiated concerns about deficits and debts, noting that they mask the real issue: the unwillingness of deficit hawks to allow government to work for the good of the people.
Keywords: 330; Haushaltsdefizit; Haushaltskonsolidierung; Theorie; USA; Welt